2009
DOI: 10.2174/1874-470210902010001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Non-Opioid Analgesics Beyond Cyclooxygenase Enzyme Inhibition

Abstract: Non-opioid analgesics including both selective and non-selective cyclooxygenase (COX) inhibitors and acetaminophen are the most widely used treatments for pain. Inhibition of COX is thought to be largely responsible for both the therapeutic and adverse effects of this class of drugs. Accumulating evidence over the past two decades has demonstrated effects of non-opioids beyond the inhibition of COX and prostaglandin synthesis that might also explain their therapeutic and adverse effects. These include their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 112 publications
(139 reference statements)
1
22
0
3
Order By: Relevance
“…An induction of PGE 2 and other prostaglandins have several functions, including stimulating protein turnover (13,55,61,63), regulating tendon blood flow (33), and regulating the activity of matrix degrading enzymes (49,75). PGE 2 also appears to modulate the production of cytokines, including interleukin (IL)-6 (20,41,50). Interestingly, administration of COX inhibitors has been shown to increase the production of IL-6 in various models (20,22,57,71,72,75), including exercise (48).…”
mentioning
confidence: 99%
“…An induction of PGE 2 and other prostaglandins have several functions, including stimulating protein turnover (13,55,61,63), regulating tendon blood flow (33), and regulating the activity of matrix degrading enzymes (49,75). PGE 2 also appears to modulate the production of cytokines, including interleukin (IL)-6 (20,41,50). Interestingly, administration of COX inhibitors has been shown to increase the production of IL-6 in various models (20,22,57,71,72,75), including exercise (48).…”
mentioning
confidence: 99%
“…Supportive evidence to this is the role of hyperforin, a constituent from St. John's wart inhibits prostaglandin synthesis, which is an established antidepressant agent . Studies show that aspirin and other non‐opioid derivatives affects antinociception through monoamines like serotonin . In addition to this, the latest developments suggest that aspirin decreases the risk of depression in subjects with high plasma homocysteine .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been observed that lack of clinical therapeutic benefit of antidepressants is associated with overall activation of the inflammatory system, 32 which may be down Studies show that aspirin and other non-opioid derivatives affects antinociception through monoamines like serotonin. 61 In addition to this, the latest developments suggest that aspirin decreases the risk of depression in subjects with high plasma homocysteine. 56 It prevents hippocampal neuronal loss 57 and aberrant neurogenesis with omega 3 fatty acids 62 at cellular levels which can be attributed to its antidepressant action.…”
Section: Discussionmentioning
confidence: 99%
“…As we have stated in the introduction, all NSAIDs have the potential of augmenting endocannabinoid levels by inhibiting COX-2 (although with a weak potential) and thereby preventing degradation of endocannabinoids (6,7,22). Inhibition of COX enzymes by NSAIDs may also elevate endocannabinoid synthesis due to the availability of arachidonic acid for endocannabinoid synthesis rather than prostaglandin synthesis (6,7,22). Moreover, some of the classical NSAIDs have been shown to inhibit FAAH directly and reduce the breakdown of endocannabinoids (9).…”
Section: Figure 3: Blockade Of Antinociceptive Effect Of Systemic Admmentioning
confidence: 99%
“…Recent investigations suggest that cannabinoid receptors and augmentation of endocannabinoid activity play important roles in the antinociceptive effects of both paracetamol and dipyrone (4,5). Besides paracetamol and dipyrone, all NSAIDs are expected to increase endocannabinoid tonus both by inhibiting endocannabinoid degradation and by increasing their synthesis via COX inhibition (6,7). Accordingly, it has been proposed that the endocannabinoid system appears to be involved in the antinociceptive effect of some NSAIDs, although there are contradictory findings (6)(7)(8)(9)(10)13).…”
Section: Introductionmentioning
confidence: 99%